Cephalometric evaluation of soft tissue changes following Anterior Maxillary Osteotomy setback in Southern Dravidian population - Jebina Dennis; Packiaraj Irudayaraj; Dhineksh Kumar N; Gnanasagar Thirukonda Janardhanan; Georgeno George Lilly jennet; Kala Bagavathy (Journal of Oral Biology and Craniofacial Research)
Introduction: Anterior Maxillary Osteotomy (AMO) is one of the commonly done orthognathic surgical procedure in maxilla. Though a lot of research have been done in the Caucasian population regarding soft tissue changes after AMO, there are only few studies for the southern Dravidian poplation. The purpose of this study was to evaluate the soft tissue changes in association with AMO setback in the southern Dravidian population Materials and methods: The study included a series of 10 patients of age group 20–40 years who underwent AMO. Lateral cephalograms were taken for each patient 2 weeks before and 6 months after the surgery. Three parameters namely, nasolabial angle, upper lip protrusion and interlabial gap were used to evaluate the soft tissue changes. Results: Mean values of pre and post-surgery were taken for nasolabial angle, upper lip protrusion and interlabial gap and were compared. Soft tissue changes in all the three parameters were found to be statistically significant. Conclusions: From the limited evidence of the study, it can be concluded that soft tissue changes following AMO setback in southern Dravidian population and the Caucasian population are almost similar.